2019
DOI: 10.1002/aisy.201900079
|View full text |Cite
|
Sign up to set email alerts
|

Gallium‐Based Thin Films for Wearable Human Motion Sensors

Abstract: Wearable electronic circuits based on the films of gallium and its alloys offer promising implementations in health monitoring and gaming sensing applications. However, the complex rheology of liquid metals makes it challenging to manufacture thin gallium-based devices with reliable, reproducible, and stable properties over time. Herein, the surface coating and topography of silicone substrates are engineered to enable precisely defined, micrometer-thick liquid metal patterns over large (>10 cm 2 ) surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…The dominant working principle of the liquid metal-based stretchable strain sensors is the geometrical effect. [167][168][169][170][171] In the following sections, it will be shown that the contribution of this mechanism to the overall sensing performance of nanomaterials-based stretchable sensors may not be significant.…”
Section: Geometrical Effectmentioning
confidence: 99%
“…The dominant working principle of the liquid metal-based stretchable strain sensors is the geometrical effect. [167][168][169][170][171] In the following sections, it will be shown that the contribution of this mechanism to the overall sensing performance of nanomaterials-based stretchable sensors may not be significant.…”
Section: Geometrical Effectmentioning
confidence: 99%
“…With the rapid development of the information industry and human-machine interface technology in recent years, VR technology and augmented reality (AR) technology have become a hot research topic when combined with MEMS/NEMS wearable devices to form a whole interactive system in 3D space. This kind of interactive system provides users with a more immersive experience and has the potential to be used in many application scenarios, such as sports training simulation, medical rehabilitation, entertainment and so on [172,174,[189][190][191][192][193][194]. Apart from the software part which providing an actual interactive 3D environment, the integrated sensors collecting user's motion, force, and tactile sensation information [195][196][197] also play an important role in the whole VR/AR interactive system.…”
Section: Toward Vr and Armentioning
confidence: 99%
“…These fingertip touch sensors characterized high sensitivity and fast response time and successfully converted fingertip events into visual control and interactive feedback in VR space (Figure 13c). Furthermore, Dejace et al proposed a finger bending strain sensor based on stretchable gallium-based conductors and a virtual-reality scenario was demonstrated to accurately monitor human hand kinematics according to sensors' resistance change as shown in Figure 13d [191]. These wearable human motion sensors, though capable of high flexibility and stretchability, can only collect limited sensory information due to their minimalist structural design.…”
Section: Toward Vr and Armentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yu et al have developed mechanical vibratory tactile device on the human skin which can mimic the touch feeling virtually . Dejace et al have utilized gallium‐based strain sensor to detect the body motion in virtual‐reality scenario . On the surgical tool side, tactile sensors integrated with the da Vinci surgical robots have been reported by different groups .…”
Section: Introductionmentioning
confidence: 99%